Dynamic Changes of Fecal Calprotectin and Related Clinical Factors in Neonates - Park, Ji Sook; Cho, Jae Young; Chung, Changyeong; Oh, Seong Hee; Do, Hyun-jeong; Seo, Ji-Hyun; Lim, Jae Young; Park, Chan-Hoo; Woo, Hyang-Ok; Youn, Hee-Shang (Frontiers in Pediatrics, 2020)
Objective: Fecal calprotectin (FC) has been widely used for a clinical marker of intestinal inflammation in children and adults. However, the clinical usefulness has not been determined in neonates. The purpose of this study was to investigate the change of FC and associated clinical factors in neonates. Method and Materials: In total, 146 neonates among 472 admissions to our NICU between 2018 and 2019 were included, and 242 stool samples were collected. FC was measured in the first, second, and third-fourth week after birth, respectively, using commercial ELISA. The clinical characteristics were reviewed from medical records. Statistical analyses were performed to analyze associated factors regarding on changes of fecal calprotectin. Results: A wide range from 5.5 to 6,000 mg/kg of FC was observed in neonates. FCs during neonatal period were not correlated with the gestational age at birth or birth weight. The meconial calprotectin was higher than FCs after two weeks of age (n=134, 418.06 vs 243.12 in the second week and 259.58 in the third week after birth). Meconial calprotectin was associated with birth weight and meconium stained amniotic fluid. FC during the neonatal period decreased with postnatal week (-464.93±158.02 at third-fourth week after birth compared with the first week, P=0.004) and breast milk (-337.27±150.51 compared with formula milk, P=0.026). Conclusion: Fecal calprotectin tended to decrease with postnatal week during the neonatal period, and breast milk could affect more decrease of FC.